Three-dimensional coronary artery reconstruction based on single-plane angiography and intravascular ultrasound registration - Beeran Kutty, Suhaili (2020)
The mortality rate of heart failure or heart disease has been increasing all over the world. Coronary artery disease (CAD) is one type of heart disease that is caused by the atherosclerosis process. The process starts with the building up of plaque along the inner walls of the coronary arteries. The obstruction of the artery will reduce the blood flow that circulates through the heart. The reduced blood flow to the heart can cause angina or chest pain and heart attack. X-ray coronary angiography is the gold standard test to investigate the affected artery, however, this modality only visualizes the silhouette of the artery. To help the diagnostic process, Intravascular Ultrasound (IVUS) based on ultrasound technology, is used to show the internal structure of the artery. Coronary angiography and IVUS complement each other. However, to use coronary angiography and IVUS simultaneously, cardiologists view both modalities on the same screen, but in a different window. They are merged mentally using the biological landmarks on the modalities and also based on the cardiologist’s knowledge and experiences. Mental registration can cause errors in the interpretation of the plaque and is time-consuming. Because of that, research on the registration of Angiography and IVUS have been highlighted until today. Most of the previous registration approaches are based on the bi-plane Angiography that required greater radiation dose and a common technique for the registration, based on the epipolar geometry. The disadvantages of this technique are that it requires at least two views of coronary angiography, and approximation is used in determining the correspondence points. In this research, the registration proposes to use a single-plane Angiography, which is the medical imaging technology that is still relevant and used in many catheterization labs around the world to reconstruct the 3D artery based on the registration with IVUS modality. Firstly, the IVUS modality; the catheter shape, the lumen and the mediaadventitia are completely segmented using labeling and a parametric deformable model. Next, the trajectory of the artery is reconstructed based on the catheter path of IVUS and the biological landmarks found on the coronary angiography image. A new method for reconstructing 3D coronary artery based on the circle trigonometry equation for the registration of single-plane coronary angiography and IVUS was introduced in this research. To help the CAD diagnostic process, this research offers an accurate measurement of the lumen cross-sectional area, minimum lumen diameter, and maximum lumen diameter. In IVUS segmentation, the result shows that 100% of the catheter shape on IVUS image is detected correctly using the labelling approach. The accuracy of the lumen segmentation increases with a percentage of area difference (PAD) 0.07, and the media-adventitia segmentation could be done without manual initialization process. It is also proven that the trajectory of the artery could be generated using only one view of Angiography that contains the catheter path of IVUS. Furthermore, the accuracy of the equation used in the registration experiment is acceptable, where it is shown by is 0.9999 more than the significant value. As a result, the new approach of the registration of the single-plane Angiography and IVUS to produce a 3D coronary artery is accepted by the medical practitioners. The 3D model shows the precise location of the catheter in the artery and the coronary artery is measured through the cross-sectional area of the lumen and the minimum and maximum diameters. The result of this study may help us to understand the longitudinal view of the coronary artery and the morphology of the arterial wall. It could be used by cardiologists to make decisions in diagnosing coronary artery disease.